Multivariate analysis of bathymetry in the evaluation of reservoirs in Serra Talhada, Pernambuco, Brazil - Bezerra, Alan Cézar; Shinozaki-Mendes, Renata Akemi; Moura, Geber Barbosa de Albuquerque (Revista Agrogeoambiental, 2020)
The constant demand for water resources has increased the need for research and adoption of new water use and management practices. In this sense, this work utilizes multivariate cluster analysis to identify the correlation of respective depths of bodies of water in Serra Talhada city, over different periods of rainfall. In order to achieve this, four bathymetric surveys were carried out during one year for three reservoirs within the municipality of Serra Talhada, then cluster analysis and multiple modeling were used to identify the most influential variables on reservoir depth. Based on our results, the multivariate grouping technique can be used to define periods of higher and lower water storage, through bathymetric data, as well as to understand the effects of regional precipitation variability on the water levels of reservoirs. In addition, the generated model indicated a clear influence of the previous month’s precipitation on the bathymetry of the reservoirs.